An evaluation of wind turbine waste heat recovery using organic Rankine cycle. (20th March 2019) - Nematollahi, Omid; Hajabdollahi, Zahra; Hoghooghi, Hadi; Kim, Kyung Chun
Abstract: Wind turbine size has increased to megawatt capacity, and the related technologies and facilities have improved, including the cooling systems. Currently, all of the heat generated by wind turbine components is wasted to the environment. This study presents a conceptual design of a novel method for waste heat recovery of a wind turbine using an organic Rankine cycle (ORC). An organic Rankine cycle is implemented to the wind turbine as a part of the cooling system. The proposed system is thermodynamically modeled to evaluate the amount of recovered energy. Seven working fluids are chosen and investigated in the simulations to estimate the working fluid effect. The results revealed that the organic Rankine cycle can be a suitable choice for cooling wind turbines while simultaneously produce the power. Both exergy and energy analysis are conducted. A maximum power of 7.1 kW is provided by the proposed system using R134 when 20 K superheat is utilized. While R600a and SE36 stand on the next place. Furthermore, a minimum of 6.25 kW power is achievable. The generated work can be used as pump driving or electricity generation. In the next step, the thermal efficiency and total annual cost are optimized simultaneously using a multi-objective optimization for R134a as best working fluid in the thermodynamic viewpoint. It is found that the ideal efficiency of the system is obtained to be 14.7% with the total price of 7050 /year. Finally, the effects of design parameters on the efficiency are obtained. Highlights: A novel method for wind turbine cooling using organic Rankine cycles is proposed. The proposed method can produce power while is cooling the wind turbine. ORC is modeled in both energy and exergy approach with different working fluids. A multi-objective optimization is applied for economical evaluation. A 7.1 kW power is utilized through the wind turbine cooling using R134.